2011
DOI: 10.1159/000327504
|View full text |Cite
|
Sign up to set email alerts
|

Breast Sonography – 2D, 3D, 4D Ultrasound or Elastography?

Abstract: The aim of this publication is to give an answer to the question whether 2D, 3D and 4D sonography of the breast can be replaced by elastography or whether elastography is an adjunct tool to B-mode imaging. The Breast Imaging and Reporting Data System (BI-RADS) ultrasound (US) descriptors of a lesion besides vascularity are based on B-mode imaging. US elastography displays the mechanical tissue properties. This information can be obtained by freehand compression and decompression. Acoustic radiation force impul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 38 publications
0
22
0
4
Order By: Relevance
“…The tissue compression might still be operator dependent, and even a slight touch of the skin might influence the elastography result [10]. Few studies on SWUE have reported the choice of the region of interest (ROI)’s size [1], [8], while its effect on SWUE measurements has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The tissue compression might still be operator dependent, and even a slight touch of the skin might influence the elastography result [10]. Few studies on SWUE have reported the choice of the region of interest (ROI)’s size [1], [8], while its effect on SWUE measurements has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing copies of a stored volume allows several trainees to be taught at the same time to recognize the fetal anatomy hidden within the volume [4,16]. 25 years after the introduction of three-dimensional ultrasound in clinical diagnostics, 3 D/4 D ultrasound provides such a broad diagnostic spectrum in the daily routine that it has become a fixture in targeted prenatal diagnosis as well as in the clarification of gynecological findings [21, 32 -35], pelvic floor defects [36], and in breast diagnostics [37]. The same is also true for various other areas of specialization [38 -40].…”
Section: Years Of 3 D Ultrasound In Prenatal Diagnosismentioning
confidence: 99%
“…Оценивая роль различных вариантов эластографии в современной УЗИ-диагностике, C. Weismann et al подчеркивают, что эластография не является самосто-ятельной диагностической методикой, но является разумным дополнением к стандартному УЗИ [21][22][23].…”
Section: Every Year More Than 1 Million New Cases Of Breast Cancer Arunclassified